2009
DOI: 10.1021/jf803243w
|View full text |Cite
|
Sign up to set email alerts
|

Prolamin Hydrolysis and Pentosan Solubilization in Germinated-Rye Sourdoughs Determined by Chromatographic and Immunological Methods

Abstract: The assortment and quality of bakery products designed for celiac patients may be improved by designing whole grain ingredients with low residual prolamin contents. The main objective of this study was to evaluate the extent of prolamin hydrolysis and pentosan solubilization in germinated-rye sourdoughs (GRSDs). Size-exclusion chromatography analyses, the fate of fluorescent prolamin, and immunological analyses determined the extent of prolamin hydrolysis and pentosan solubilization. Hydrolysis of rye prolamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 35 publications
2
40
0
3
Order By: Relevance
“…Prolonged incubation of wheat and durum fully degraded gliadins (Bigiarini and others ; Stenman and others ; Schwalb and others ). Germinated and fermented rye and wheat sourdough effectively degraded 99.5% and 95% of prolamins, respectively (Loponen and others , ). Specifically, the toxic 12‐mer of α‐gliadin QLQPFPQPQLPY was hydrolyzed in gliadin treated with germination enzymes (Stenman and others , ).…”
Section: The Impacts Of Food Processing On Wheat Sensitivitymentioning
confidence: 98%
See 1 more Smart Citation
“…Prolonged incubation of wheat and durum fully degraded gliadins (Bigiarini and others ; Stenman and others ; Schwalb and others ). Germinated and fermented rye and wheat sourdough effectively degraded 99.5% and 95% of prolamins, respectively (Loponen and others , ). Specifically, the toxic 12‐mer of α‐gliadin QLQPFPQPQLPY was hydrolyzed in gliadin treated with germination enzymes (Stenman and others , ).…”
Section: The Impacts Of Food Processing On Wheat Sensitivitymentioning
confidence: 98%
“…As a positive marketing aspect, germinated grain can improve flavor. Loponen and others () reported that rye sourdough made from germinated grain had enhanced flavor compared to bread made from nongerminated grain.…”
Section: The Impacts Of Food Processing On Wheat Sensitivitymentioning
confidence: 99%
“…The oat protein samples were analyzed with SE-HPLC as described by Loponen et al (2009) with modifications. The oat protein samples were extracted 1:100 by 1.5% SDS, 50 mM sodium phosphate, pH 6.9 buffer, at 50 C overnight and then centrifuged at room temperature (10 min, 10 000 Â g).…”
Section: Size-exclusion High-performance Liquid Chromatography (Se-hpmentioning
confidence: 99%
“…Previously, we showed that sourdough fermentation conditions are very favourable for the germination-induced enzymes to hydrolyse the prolamins. More specifically, we noted that 95% of the wheat and 99.5% of the rye prolamins degraded under sourdough conditions when enzyme active malts were used as raw materials (Loponen et al, 2007(Loponen et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%